2021
DOI: 10.1016/j.psychres.2021.114228
|View full text |Cite
|
Sign up to set email alerts
|

Suicide, self-harm and suicidal ideation during COVID-19: A systematic review

Abstract: We aimed to do a systematic review and meta-analysis of studies describing suicidal ideation, suicide attempts and suicide and associated risk factors during COVID-19 pandemic. We searched following electronic databases using relevant search terms: Medline, Embase, PsycInfo and CINAHL and systematically reviewed the evidence following PRISMA guidelines. The meta-analysis of prevalence of suicidal ideation was done using random effect model. The search returned 972 records, we examined 106 in full text and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
121
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(193 citation statements)
references
References 77 publications
9
121
1
11
Order By: Relevance
“…The COVID-19 pandemic has imposed a slow and long-term burden on society and individuals compared to severe natural disasters such as earthquakes and tsunamis. Indeed, increasing suicide mortality rates are concerning due to the prolongation of the COVID-19 pandemic, since the rate of suicidal ideations during the COVID-19 pandemic is higher than that reported in studies on the general population during the pre-pandemic period [ 39 ]. Therefore, the long-lasting burden on societies and individuals induced by the COVID-19 pandemic is fundamentally different from that of previous natural disasters and economic crises.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has imposed a slow and long-term burden on society and individuals compared to severe natural disasters such as earthquakes and tsunamis. Indeed, increasing suicide mortality rates are concerning due to the prolongation of the COVID-19 pandemic, since the rate of suicidal ideations during the COVID-19 pandemic is higher than that reported in studies on the general population during the pre-pandemic period [ 39 ]. Therefore, the long-lasting burden on societies and individuals induced by the COVID-19 pandemic is fundamentally different from that of previous natural disasters and economic crises.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed a larger suicidal ideation increase than suicidal attempts, suggesting the possibility of higher suicide rates in the future. According to that, a recent first meta-analysis estimate of suicidal ideation based on a large sample from different countries and populations has shown the rate of suicidal ideations during COVID-19 pandemic was higher than that reported in studies on the general population prior to the pandemic [ 20 ]. The increase in suicidal ideation in the COVID-19 year is coherent with the rise of anxiety, stress, and depression, related to the protracted period of lockdown and the interruption of educational and sport activities, known risk factors for the development of self-injury and suicidal behaviours [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to self-injuring, it seems that the second wave of the COVID-19 pandemic, in particular, has significantly affected suicide rates among children and adolescents [ 19 ]. Specifically, months with significantly higher rates of suicide-related behaviours appear to correspond to times when COVID-19–related stressors were heightened [ 20 ]. With respect to suicidal behaviours, an observational retrospective study conducted in France from January 2018 to June 2020 found that, during the COVID-19 lockdown (March–May 2020), the number of hospitalisations for suicidal behaviours in children and adolescents decreased by 50% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews and meta‐analyses suggested that the prevalence of COVID‐19 pandemic time CMHS and suicidal behavior was higher among different cohorts worldwide 12,53 . Previous studies have found the association between COVID‐19 related factors and CMHS and suicidal behavior among students and young adults in Bangladesh 54,55 .…”
Section: Discussionmentioning
confidence: 99%